2008
DOI: 10.1002/ejoc.200701219
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Silylformylation Products Derived from Alkynes

Abstract: The silylformylation reaction of unsaturated compounds consists of the rhodium-catalysed addition of a R 3 Si and a CHO moiety to a carbon-carbon multiple bond. The silylformylation process is applicable to both terminal and internal alkynes and is tolerant towards several functional groups. Many factors can influence the chemoselectivity of the reaction that generally affords β-silylalkenals with high yields and regioselectivity. The β-silylalkenals are polyfunctionalised substrates that can be submitted to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 116 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…Carbon monoxide and isocyanides are potentially interesting 1,1-insertion substrates for hydrosilations, but little is known concerning this possibility. Silylformylations, involving the coupling of a silane, CO, and an alkene or alkyne, are known, and the catalytic 1,1-hydrosilation of isocyanides has only been reported for the reaction of CyNC with Et 3 SiH using Cu(acac) 2 as a catalyst . Furthermore, the formyl and iminoformyl silane products that might result from insertions into an Si–H bond are attractive synthetic targets as useful chemical intermediates that are difficult to prepare by other methods .…”
mentioning
confidence: 99%
“…Carbon monoxide and isocyanides are potentially interesting 1,1-insertion substrates for hydrosilations, but little is known concerning this possibility. Silylformylations, involving the coupling of a silane, CO, and an alkene or alkyne, are known, and the catalytic 1,1-hydrosilation of isocyanides has only been reported for the reaction of CyNC with Et 3 SiH using Cu(acac) 2 as a catalyst . Furthermore, the formyl and iminoformyl silane products that might result from insertions into an Si–H bond are attractive synthetic targets as useful chemical intermediates that are difficult to prepare by other methods .…”
mentioning
confidence: 99%
“…This indicates that silylimination with equimolar amounts of tertiary-alkyl-substituted isocyanides, such as tert -butyl isocyanide and 1,1,3,3-tetramethylbutyl isocyanide ( tert -octyl isocyanide), and hydrosilanes results in the formation of Z isomers, while the use of an aryl-substituted isocyanide gave E isomers. In the related silylformylation reaction, in which carbon monoxide is used in place of isocyanides, Z isomers were obtained stereoselectively . During the course of our study on the Z -selective silylimination of primary-alkyl-substituted alkynes with tert -octyl isocyanide, however, we found that α-silylmethyl-α,β-unsaturated imines B , which contain an allylsilane, were also formed when an excess molar amount of hydrosilane relative to isocyanide was used in the reaction.…”
Section: Introductionmentioning
confidence: 88%
“…70 Bäckvall recently demonstrated that reaction of the vinylcuprate intermediate with allylic phosphinates can be tuned to give linear or branched products. 71 A specific carbosilylation that can be achieved with a single combination of reagents is rhodium-catalysed silylformylation 72 -a reaction which proceeds via synsilylrhodation of a carbon-carbon triple bond, followed by insertion of carbon monoxide into the vinylrhodium species, to provide stereodefined 1,2,2-trisubstituted b-silylenals (e.g. 40, Scheme 19, equation 1).…”
Section: 22-trisubstituted and Tetrasubstituted Vinylsilanesmentioning
confidence: 99%